(untitled) (Journal of College of Medical Sciences-Nepal, 2021)
Background: Gastrointestinal malignancy constitutes a significant cancer burden in terms of mortality. They are most often detected late due to hidden location and lack of symptoms. This study was undertaken with an aim to see age and site distribution, histopathological spectrum, histologic grade and pathologic stage at presentation and to find correlation between histologic grade and pathologic stage at presentation. Methods: This retrospective chart review was carried on 161 cases of GI malignancies received in Department of Pathology of College of Medical Sciences and Teaching Hospital during a time period of 8 years from January 2012 to December 2019. Results: Age of the patients ranged from 16 to 93 years with a mean±SD of 57.3±16.3 years with maximum 36 (22.4%) cases in 51-60 years age group and a male female ratio of 1.4:1. 29 (18.0%) cases were seen at or below 40 years of age. Stomach was the most common site involved in 69 (42.9%) cases. Majority, 136 (84.5%) cases were adenocarcinoma. Majority, 48 (35.3%) cases of adenocarcinoma were Grade 2. Most 31 (45.0%) cases were Stage III at presentation. There was no statistical significant association between histologic grade and pathologic stage (p = 0.073). Conclusion: GI malignancy constitutes a significant cancer burden. Younger individuals are also considerably affected denoting a need of high degree of suspicion. Stomach was the most common site involved. Adenocarcinoma was the most common histological type. There was no association between histologic grade and pathologic stage at presentation (p > 0.05).